Joseph in the Qurʾān, a Prophetic Narrative. Incidents and Specific Language - Cuciniello, Antonio (Folia Orientalia, 2026)
The object of the essay is prophecy in the Qur’ān, through the stories of the prophets and the language they use. Specifically, the Qur’ānic narrative and Joseph’s speeches have been systematically examined, with the intention of introducing a symmetrical reading of the story between incidents and the specific language. Emphasis has been placed on the philological aspects, by focusing the analysis on the Arabic version of the Qur’ān, in order to try to draw up a personal profile of Joseph and, at the same time, to attempt to counter an approach that claims to see all the Qur’ānic envoys only in their instrumental function in the mission of Muḥammad.